Network Development for Community-Based Tourism of the Wang Riverside Communities, Mueang District, Lampang Province - Wattanasup, Pattharawadee (Graduate Review of Political Science and Public Administration Journal, 2023)
The objective of this research is to study network construction, network maintenance, and methods for community-based tourism network development with collaboration from all 3 Wang Riverside community groups under the supervision of Lampang City Municipality, Mueang District, Lampang Province (namely, Ta Ma O community group, Baan Pong Sanuk community group, and Kad Kong Ta community group). Qualitative research methods were used for this study. Specific data was collected from 24 purposive samples who have duties relating to community-based tourism. These samples come from the public sector, government sector, and private sector. Data was collected via in–depth interviews, focus group interviews, and documentary study. The result shows that there are 2 overlapping patterns of network building, which are formal community network and community-based tourism network. The main elements of all community networks are the local government organization and the community members in a collaborative, decentralized model. There are different ways to participate in many activities in order to maintain their relationships. Nevertheless, there is still a problem with a lack of leaders coming from the new generation. However, for collaboration network development, a government agency should be involved as a middleman to coordinate and support in conducting meetings for reaching agreements and to hold special tourism activities.